RECENT ADVANCEMENT IN FORENSIC TOXIC DRUG ANALYSIS BY DESORPTION ELECTROSPRAY IONIZATION MASS SPECTROMETRY (DESI-MS) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Forensic toxicology is the analysis of biological samples to identify the presence of any harmful substances in the body. The three major sub disciplines in forensic toxicology are; human performance toxicology, post-mortem toxicology and forensic drug analysis. Hence, from the three major sub disciplines in forensic toxicology, forensic drug analysis is of major interest, as it involves in the identification of illicit and counterfeit pharmaceutical drugs in biological matrices.Thus, desorption electrospray ionization mass spectrometry (DESI-MS) is an emerging technique in rapid analysis of biological samples in forensic drug analysis, due to the increase in illicit and counterfeit drug users during the past decade. Although, this technique allows the direct analysis of samples from the surface at ambient pressure, development in the technique has been made to increase the sensitivity and specificity in analysing forensic drugs. Meanwhile, improvements in the extraction procedures prior to DESI-MS analysis, possibilities in analysing the drugs in raw urine sample from its native environment and reduction in the geometrical parameters have been the major developments made in DESI-MS. Also, advancement in DESI-MS enables direct analysis of drug tablets to identify the active pharmaceutical drugs present in the tablet and distinguishes between pharmaceutical drugs and counterfeit or fake drugs. This safety evaluation is important as several counterfeit drugs are prepared with illicit components and sold in the market and used to perform illegal activities. Therefore, the recent advancement in forensic toxic drug analysis by DESI-MS enables the law enforcement to pursue criminal charges against the suspect.